Determinants of psychological distress among individuals who are aware of their HIV serostatus in South Africa: findings from the 2017 national HIV prevalence, incidence, behavior, and communication survey - Vondo, Noloyiso; Mabaso, Musawenkosi; Ginyana, Thembelihle; Malope, Lesiba; Moyo, Sizulu; Zungu, Nompumelelo; Shisana, Olive (Frontiers in Public Health, 2024)
Introduction: Psychological distress is a growing public health challenge among people living with HIV. This study investigated the prevalence of psychological distress among individuals who know their HIV positive or negative serostatus in South Africa using 2017 data from a nationwide crosssectional household-based population survey.The data for this secondary analysis was collected using a multi-stage stratified cluster randomised sampling design. Multivariable backward stepwise generalised linear regression models were fitted to determine factors associated with psychological distress as measured by the Kessler Scale (K10) among HIV-positive and HIV-negative individuals who know their serostatus in South Africa.Results: Of 18 662 participants, psychological distress was 27.4% (95% CI: 25.3-29.7) among those HIV-positive and 20.1% (95% C: 18.8-21.4) among those HIV-negative. The odds of psychological distress were significantly higher among HIV-positive individuals who rated their health as fair/poor [AOR=1.22 (95% CI: 1.09-1.35), p<0.001)], and the odds were lower among those residing in rural formal/farm areas [AOR=0.85 (95% CI: 0.78-0.93), p<0.001)], and those with tertiary education level [AOR=0.88 (95% CI: 0.78-0.99), p=0.033]. The odds of psychological distress in HIV-negative individuals were significantly higher among females than males [AOR=1.09 (95% CI: 1.05-1.14), p<0.001], high-risk alcohol drinkers [AOR=1.26 (95% CI: 1.02-1.57), p=0.035] and hazardous alcohol drinkers [AOR=1.09 (95% CI: 1.01-1.18), p=0.028] than abstainers and those who rated their health as fair/poor rather than excellent/good [AOR=1.18 (95% CI: 1.10-1.26), p<0.001].The study underscores the importance of addressing IPV, alcohol misuse and sociostructural inequalities linked to gender and race-based disparities, such as low educational attainment and unemployment, as critical factors associated with psychological distress in the study population.